White matter alterations in anorexia nervosa: A systematic review of diffusion tensor imaging studies - Martin Monzon, Beatriz (World J Psychiatry, 2016)
AIM: To identify findings concerning white matter (WM) fibre microstructural alterations in anorexia nervosa (AN). METHODS: A systematic electronic search was undertaken in several databases up to April 2015. The search strategy aimed to locate all studies published in English or Spanish that included participants with AN and which investigated WM using diffusion tensor imaging (DTI). Trials were assessed for quality assessment according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses checklist and a published quality index guideline. RESULTS: A total of 6 studies met the inclusion criteria, four of people in the acute state of the illness, one included both recovered and unwell participants, and one included people who had recovered. Participants were female with ages ranging from 14 to 29 years. All studies but one measured a range of psychopathological features. Fractional anisotropy and mean diffusivity were the main DTI correlates reported. Alterations were reported in a range of WM structures of the limbic system, most often of the fornix and cingulum as well as the fronto-occipital fibre tracts, i.e., regions associated with anxiety, body image and cognitive function. Subtle abnormalities also appeared to persist after recovery. CONCLUSION: This diversity likely reflects the symptom complexity of AN. However, there were few studies, they applied different methodologies, and all were cross-sectional.